P.132: Enhancing the Visual Performance of Touch Screen Displays. Issue 1 (1st July 2013) - Grabski, Greg; Robinson, Tim
Abstract: Properly designed touch screens are bringing previously unattainable levels of intuitive human‐computer interactions for managing aircraft information. Human‐factor issues, such as the visual appearance of the display in high ambient sunlight conditions, avoidance of accidental activation, and resistance to the deposition of fingerprints, are all influenced by the touch screen construction and integration with the active matrix liquid crystal display (AMLCD). This paper describes a touch screen display designed with Human‐Machine‐Interface (HMI) features required for flight deck applications.